2021
DOI: 10.1101/2021.09.27.462031
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immune function of the serosa in hemimetabolous insect eggs

Abstract: Insects comprise more than a million species and many authors have attempted to explain this success by evolutionary innovations. A much overlooked evolutionary novelty of insects is the serosa, an extraembryonic epithelium around the yolk and embryo. We have shown previously that this epithelium provides innate immune protection to eggs of the beetle Tribolium castaneum. It remained elusive, however, whether this immune competence evolved in the Tribolium lineage or is ancestral to all insects. Here, we expan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Data accessibility. The data are provided in the electronic supplementary material [79]. The sequencing data discussed in this publication have been deposited in NCBI's Gene Expression Omnibus [33] and are accessible through GEO series accession number GSE100429 (https://www.…”
Section: Discussionmentioning
confidence: 99%
“…Data accessibility. The data are provided in the electronic supplementary material [79]. The sequencing data discussed in this publication have been deposited in NCBI's Gene Expression Omnibus [33] and are accessible through GEO series accession number GSE100429 (https://www.…”
Section: Discussionmentioning
confidence: 99%
“…to be adaptive and related to certain environments or behaviours (Briscoe et al 2013;Cheng et al 2017;Rane et al 2019;Chakraborty et al 2021). The Shx genes are expressed in the serosa during development, an extraembryonic tissue implicated in innate immunity and desiccation resistance in insects (Panfilio 2008;Jacobs et al 2013Jacobs et al , 2014Jacobs et al , 2022. It is therefore possible that Shx duplication is an adaptation associated with modifications to the egg, and indeed many of the highly duplicated genes show increased rates of sequence evolution (Figure 4A).…”
Section: Moths Take the Record For The Most Hox Locimentioning
confidence: 99%
“…[48,51]). Downstream, RNA-seq after RNAi and pathogen-challenge studies have identified factors for serosal tissue maturation and physiology [24,55,56].…”
Section: Deciphering the Genetic Signature Of The Amnionmentioning
confidence: 99%
“…Many purported tissue-scale functions of polyploidy are probably applicable in this outer EE tissue. Serosal tissue integrity as a barrier epithelium of large cells confers cellular protection via detoxification [130] and innate immune responses to infection [55,56]. Furthermore, in many insect species, the serosa secretes a substantial cuticle that provides desiccation resistance [131133] and mechanical protection [24].…”
Section: Polyploid Genomic Architectures Underpin Extraembryonic Tiss...mentioning
confidence: 99%